Physical activity in leisure, aerobic capacity perceived and subjective wellness of physical education academics throughout the course - Meira, Carlos Eduardo Vieira (2019)
Objective: To identify how the variables: physical activity in leisure, aerobic perceived capacity and the subjective well-being of academics during the course of Physical Education. Method: For this study, three instruments were used: the Personal Welfare Scale (PWI), Leisure Practice Scale and the Aerobic Perceived Capacity Scale. We evaluated 115 academics (79 women and 36 men), with a mean age of 25.01 (6.2) years. Results: We evaluated 115 academics (79 women and 36 men), with a mean age of 25.01 (6.2) years. It was identified that 87.5% of the students were considered physically active at the beginning of the course, 95.5% in the middle and 91.3% at the end. Already for high aerobic capacity perceived, the results were 41.7% at the beginning, 40.9% in the middle, and 30.4% at the end. Concerning subjective well-being, 25.0% at the beginning, 22.7% at the middle and 34.8% at the end of the course were classified with high satisfaction with life. Conclusions: Due to these results, it is suggested that, during graduation, with the achievement of knowledge about Physical Education, the academics improved their subjective perception about physical capacity and improved well-being.